Ed "Doc" Ricketts - George A. Robinson:::Creator::::::::::::
Ed 'Doc' Ricketts sitting at his desk and reading at Pacific Biological Laboratory, Ed Ricketts lab, 800 Cannery Row. Reported as his last photograph taken by George A. Robinson (1913-1979) Ricketts' friend & the personnel manager at California Packing Company from 1950-1972) . Original is in the safe.